An exception to the matched filter hypothesis: A mismatch of male call frequency and female best hearing frequency in a torrent frog. Issue 1 (20th December 2016) - Zhao, Longhui; Wang, Jichao; Yang, Yue; Zhu, Bicheng; Brauth, Steven E.; Tang, Yezhong; Cui, Jianguo
Abstract: The matched filter hypothesis proposes that the tuning of auditory sensitivity and the spectral character of calls will match in order to maximize auditory processing efficiency during courtship. In this study, we analyzed the acoustic structure of male calls and both male and female hearing sensitivities in the little torrent frog ( Amolops torrentis ), an anuran species who transmits acoustic signals across streams. The results were in striking contradiction to the matched filter hypothesis. Auditory brainstem response results showed that the best hearing range was 1.6–2 kHz consistent with the best sensitive frequency of most terrestrial lentic taxa, yet completely mismatched with the dominant frequency of conspecific calls (4.3 kHz). Moreover, phonotaxis tests show that females strongly prefer high‐frequency (4.3 kHz) over low‐frequency calls (1.6 kHz) regardless of ambient noise levels, although peripheral auditory sensitivity is highest in the 1.6–2 kHz range. These results are consistent with the idea that A. torrentis evolved from nonstreamside species and that high‐frequency calls evolved under the pressure of stream noise. Our results also suggest that female preferences based on central auditory system characteristics may evolve independently of peripheral auditory system sensitivity in order to maximize communication effectiveness in noisy environments. Abstract : The matched filter hypothesis is an important principle in evolutionary biology. Here, we show an important exception for a frog species that inhabits a noisy streamside environment. In this species, the receiver's peripheral auditory frequency sensitivity is mismatched completely with male acoustic signals, which are higher in frequency than those of sympatric and lentic species whose calls are not masked by stream noises.